FORMULASI DAN UJI PELEPASAN KRIM EKSTRAK ETANOL DAUN JAMBU BIJI DENGAN POTENSI ANTIJERAWAT - N. P. Y. A. Dewi; N. L. G. W. Pebriani; P. A. Duarsa; P. C. I. Warnaya; I. D. A. A. D. Candraningrat; C. I. S. Arisanti (Jurnal Kimia (Journal of Chemistry), 2020)
Guava leaves contain quercetin which can inhibit the growth of Propionibacterium acne. Thus, guava leaves have the potential to be anti-acne. Based on the benefits of guava leaves, it is necessary to formulate the ethanol extract of guava leaves in cream preparation and its characterization as well as to know the rate of releasing active substances. Preparation and standardization of guava leaf simplicia was carried out. After that, maceration, standardization and phytochemical screening of guava leaf ethanol extract were done. Positive extracts containing flavonoids were formulated into cream preparation. The concentration of stearic acid as emulgator of 14% and 18% was optimized. The formula was tested for physical and chemical properties such as organoleptic, spreadability, adhesion, viscosity and pH. The optimum formula was characterized using Franz diffusion test to determine the release of the active substance. The results showed that concentration of stearic acid as emulgator influenced the physical and chemical properties of the cream. Based on the results of this study it could be concluded that the optimum formula was stearic acid concentration of 14% with the release active substances for 3 hours of 2,5882 mg. Keywords: Guava leaves, acne, cream, stearic acid, diffusion